Effect of Humic Acid Applications on Yield, FruitCharacteristics and Nutrient Uptake in Ercis Grape (V. vinifera L.) Cultivar - Cangi, Rustem; Tarakcioglu, Ceyhan; Yasar, Harun (Asian Journal of Chemistry, 2010)
The effects of humic acid applications on the yield, fruit characteristics and nutrient uptake of Ercis grape cultivar (V. vinifera L.) in Van in the east of Turkey were examined during two growing seasons in 2003-2004. Solid form of humic acid (55% humic acid, 30% fulvic acid and 8% K2O) were applied from soil in the amount of 100, 200, 300 kg/ha and 10, 20, 30 kg/ha from leaves. There was no significant effects of humic acid application on the yield and mean bunch weight (MBW) but there was significant effect on soluble solid contents (SSC) and total acid statistically. SSC content was increased with humic acid applications, but total acid was decreased with treatment. As a result of this study, yield, MBW, SSC total acid ranged between 6650 and 14580 kg/ha, 123.3 and 249.5 g, 12.3 and 18.0%, 1.28 and 2.05 g/L, as years and applications, respectively. In the result of leaf analysis, humic acid affected the N content (each two years), P, Fe and Zn contens of leaves (at first year), but K, Cu and Mn contents were not affected statistically. N and K content of leaves were increased with humic acid applications as compared with control. As a result, SSC, total acid, N and Fe contents of leaves of grape vines were affected by humic acid application. In cool ecology, such as Van province, increase in SSC by humic acid application will contribute to ripening of grapes before autumn frost.